Relação entre câncer e alergia - Bruno Gustavo Muzzi Carvalho e Carneiro (2011)
Justification: Cancer represents a severe threat to world health and is the second most common cause of death in Brazil. As such, it has become necessary to investigate the possible factors that cause cancer, such as environments related to life styles, as well as biological environments, including the role of the immune system. Many studies have suggested an inverse association between allergies and cancer, while others have found no relation between them, and still others have shown an increased risk of cancer in allergy patients. The conflicting findings from prior studies are partially due to the chosen research method, such as different definitions and measures for atopy, in addition to variations in the control of confusion factors, such as smoking and obesity. It is important to note that the majority of studies were carried out in a wide range of countries, using a diversity of research methods. Objectives: Verify if there is in fact a relation between certain types of cancer and allergies; investigate if there is a difference between individuals with and without cancer in relation to allergies. Methods: Case-control study carried out at the Alberto Cavalcanti Hospital of the Hospital Foundation of the State of Minas Gerais (FHEMIG) from 2009 to 2011. The study included patients of over 18 years of age, from both genders, who presented a diagnosis of cancer, as compared to healthy individuals, paired by gender and age. An anamnesis was gathered considering the medical history of the allergy, as diagnosed by a doctor, as well as the patients habits, associated illnesses, and the use of medications. For cancer patients, data concerning the tumor were recorded. Subsequently, an allergy percutaneous test was performed in each group to detect allergic hyperreactivity toward common inhalable, bacterial, and food antigens within our everyday environment. A blood sample was collected to quantitatively evaluate the eosinophils. Results: groups were paired according to interest variables, and eventual deviations were adjusted by means of multivariate analysis. Reports of allergies occurred in 30% of the patients in the cancer group, as compared to 53% in the control group (p<0.05), whereas in the cutaneous tests, a greater positivity occurred in the cancer group (69%) than in the control group (51%, p<0.05). No difference in the eosinophil values could be observed within the groups. Conclusion: Cancer patients present fewer allergies. By contrast, in cancer patients, positive cutaneous tests detected allergies which did not correspond to the clinical findings. Therefore, in cancer patients, the positive cutaneous test for allergies does not present a direct relation to the presence of clinically detectable allergies.